Synthesis and Characterization of Flexible Resistive Humidity Sensors Based on PVA/PEO/CuO Nanocomposites - Hashim, Ahmed; Al-Khafaji, Yahya; Hadi, Aseel (Transactions on electrical and electronic materials, 2019)
Synthesis of polyvinyl alcohol (PVA)–polyethylene oxide (PEO)–copper oxide (CuO) nanocomposites and studying their structural and optical properties for humidity sensors applications were investigated. The prepared humidity sensors have lightweight, low cost, flexible and high sensitivity compare with other humidity sensors. The results showed that the nanocomposites have high absorption in UV region. The absorbance of (PVA–PEO) blend increases with increase in CuO nanoparticles concentrations which may be used for solar cell, transistors, diodes and other electronic applications. The optical constants increase while the transmittance and energy gap decrease as CuO nanoparticles concentrations increase. The results of application showed that the (PVA–PEO–CuO) nanocomposites with different copper oxide nanoparticles concentrations have high sensitivity for relative humidity which may be used as sensors for different humidity ranges.